2017
DOI: 10.5194/acp-17-14291-2017
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of airborne fluorescent bioparticles in Antarctica

Abstract: Abstract. We demonstrate, for the first time, continuous real-time observations of airborne bio-fluorescent aerosols recorded at the British Antarctic Survey's Halley VI Research Station, located on the Brunt Ice Shelf close to the Weddell Sea coast (lat 75 • 34 59 S, long 26 • 10 0 W) during Antarctic summer, 2015. As part of the NERC MAC (Microphysics of Antarctic Clouds) aircraft aerosol cloud interaction project, observations with a real-time ultraviolet-lightinduced fluorescence (UV-LIF) spectrometer were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 66 publications
1
30
2
Order By: Relevance
“…Ambient measurements have been conducted worldwide using UV-LIF spectrometers, and in comparison to the MBS, for which no published ambient data currently exist, multiple versions of the WIBS have been part of worldwide measurement campaigns [21][22][23][24][25][26][27][28]. Laboratory experiments conducted using UV-LIF spectrometers are limited in relation to the quantity of ambient measurements conducted worldwide.…”
Section: Uv-lif Usagementioning
confidence: 99%
“…Ambient measurements have been conducted worldwide using UV-LIF spectrometers, and in comparison to the MBS, for which no published ambient data currently exist, multiple versions of the WIBS have been part of worldwide measurement campaigns [21][22][23][24][25][26][27][28]. Laboratory experiments conducted using UV-LIF spectrometers are limited in relation to the quantity of ambient measurements conducted worldwide.…”
Section: Uv-lif Usagementioning
confidence: 99%
“…2.3). The use of this method has been applied for analysis of data from a Colorado pine forest (Robinson et al, 2013;Crawford et al, 2014;Huffman et al, 2013;Gosselin et al, 2016), a highaltitude site in central France (Gabey et al, 2013), and the Brunt ice shelf in Antarctica (Crawford et al, 2017). This analysis has also been applied to laboratory data and has been shown to effectively segregate between polystyrene latex spheres (PSLs) of different sizes and doping (Crawford et al, 2015).…”
Section: Hierarchical Agglomerative Cluster (Hac) Analysismentioning
confidence: 99%
“…The HAC method was used to distinguish and statistically segregate different biological particle types, using the approach of Crawford et al (2015). Previous studies have reported the success of the method for data analysis in a range of environments (Gabey et al, 2013;Crawford et al, 2014Crawford et al, , 2015Crawford et al, , 2017Gosselin et al, 2016), and its use has been compared to other analysis methods, including various supervised learning techniques (Ruske et al, 2016).…”
Section: Data Sources and Analysismentioning
confidence: 99%
See 2 more Smart Citations